2015
DOI: 10.1063/1.4905368
|View full text |Cite
|
Sign up to set email alerts
|

Large area strain analysis using scanning transmission electron microscopy across multiple images

Abstract: Here, we apply revolving scanning transmission electron microscopy to measure lattice strain across a sample using a single reference area. To do so, we remove image distortion introduced by sample drift, which usually restricts strain analysis to a single image. Overcoming this challenge, we show that it is possible to use strain reference areas elsewhere in the sample, thereby enabling reliable strain mapping across large areas. As a prototypical example, we determine the strain present within the microstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…The observed strain gradient originates from lattice distortion within the alloy due to coherency strain introduced by thermal expansion mismatch between the phases. This behavior is consistent with prior investigations with other techniques characterising γ/γ interfaces in superalloys [3,21,22,26,35]. Beyond strain, lattice misfit, δ, between the γ and γ phases is another important descriptor of superalloy system, defined as:…”
Section: γγ Coherency Strainsupporting
confidence: 88%
See 2 more Smart Citations
“…The observed strain gradient originates from lattice distortion within the alloy due to coherency strain introduced by thermal expansion mismatch between the phases. This behavior is consistent with prior investigations with other techniques characterising γ/γ interfaces in superalloys [3,21,22,26,35]. Beyond strain, lattice misfit, δ, between the γ and γ phases is another important descriptor of superalloy system, defined as:…”
Section: γγ Coherency Strainsupporting
confidence: 88%
“…[3] is closer to the true unconstrained lattice misfit [21]. Furthermore, strain relaxation in the TEM specimen due to the presence of free surfaces can contribute to the partial relaxation of coherency strain [21,22,26]. In addition, the average sample region for RevSTEM analysis is smaller (∼25 nm 2 ) in comparison to the larger sample area (∼mm 2 ) for neutron diffraction.…”
Section: γγ Coherency Strainmentioning
confidence: 93%
See 1 more Smart Citation
“…However, recently it was shown that the use of multiple images and correction of the drift and scan distortions can increase the achievable FOV for HRSTEM. 16 Dark-field electron holography (DFEH) techniques, either off-axis 17 or in-line, 18 provide a larger FOV reaching up to 1 lm but require a dedicated microscope equipped with an electrostatic bi-prism or a sophisticated focal series reconstruction algorithm, respectively. In addition, both HRSTEM and holographic techniques require the sample to be in exact zone axis or two-beam diffracting condition and to have exactly the same orientation throughout the entire analyzed area.…”
mentioning
confidence: 99%
“…[3][4][5][6] Using aberration corrected STEM, the lattice distortions in materials can now be measured on a unit-cell by a unit-cell basis and at the picometer level. [7][8][9] The clear view of atom positions enables direct comparison of experiment with theory modeling. 7,8,[10][11][12] In this work, we employ the contrast based on the high-angle scattering of electrons (Z-contrast) in a STEM mode to image the cation sub-lattice only, which allows for directly measuring vacancy-induced displacements of cations in YSZ.…”
Section: Introductionmentioning
confidence: 99%